Quality Uncertainty and Perception Information Asymmetry and Management of Quality Uncertainty and Quality Perception - Wankhade, Lalit; Dabade, Balaji; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2010)
The book addresses the complex issue of quality uncertainty due to information asymmetry in the backdrop of information economics, total quality management and marketing science. Reliability Engineering, Seven Management Tools and System Dynamics are used to develop theories on quality uncertainty and perception. Quality perception is identified as a multidisciplinary measure of business performance. The tools are developed to minimize quality uncertainty or to maximize quality perception. A few worksheets are provided for applying these theories to improve business performance.
Keywords: Economics; Engineering economy; System safety; Business planning; Economics/Management Science; Organization/Planning.; Innovation/Technology Management; Production/Logistics/Supply Chain Management; Engineering Economics, Organization, Logistics, Marketing; Quality Control, Reliability, Safety and Risk